2023
DOI: 10.1002/cphc.202300124
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Exploration of C−H⋅⋅⋅X Hydrogen Bond in [CHCl3−X(CH3)2] Complexes (X=O, S, and Se)

Dhritabrata Pal,
Heena Charaya,
Shamik Chakraborty

Abstract: Among the conglomeration of hydrogen bond donors, the C−H group is prevalent in chemistry and biology. In the present work, CHCl3 has been selected as the hydrogen bond donor and are X(CH3)2 are the hydrogen bond acceptors. Formation of C−H⋅⋅⋅X hydrogen bond under the matrix isolation condition is confirmed by the observation of red‐shift in the C−H stretching frequency of CHCl3 and comparison with the simulated spectra. Stabilisation energy of all the three complexes is almost equal although the observed red‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 50 publications
(87 reference statements)
0
4
0
Order By: Relevance
“… 52–54 Very recently, the existence of C sp –H and C sp 3 –H stretching frequency red-shifts of nonconventional C sp –H⋯Se and C sp 3 –H⋯Se hydrogen bonds has been theoretically and experimentally discovered in complexes of C 8 H 6 and Se(CH 3 ) 2 , 55 Q 3 CH and SeH 2 (Q = Cl, H, and F), 56 and CHCl 3 and Se(CH 3 ) 2 . 57 It is noteworthy that a very large C sp 2 –H blue-shift of 104.5 cm −1 was reached in the complexes between CH 3 CHZ and RCZOH (R = H, CH 3 , F; Z = O, S). 54 The nonconventional C sp 2 –H⋯Se/Te and Z–H⋯Se/Te hydrogen bonds have recently been found in some systems.…”
Section: Introductionmentioning
confidence: 92%
“… 52–54 Very recently, the existence of C sp –H and C sp 3 –H stretching frequency red-shifts of nonconventional C sp –H⋯Se and C sp 3 –H⋯Se hydrogen bonds has been theoretically and experimentally discovered in complexes of C 8 H 6 and Se(CH 3 ) 2 , 55 Q 3 CH and SeH 2 (Q = Cl, H, and F), 56 and CHCl 3 and Se(CH 3 ) 2 . 57 It is noteworthy that a very large C sp 2 –H blue-shift of 104.5 cm −1 was reached in the complexes between CH 3 CHZ and RCZOH (R = H, CH 3 , F; Z = O, S). 54 The nonconventional C sp 2 –H⋯Se/Te and Z–H⋯Se/Te hydrogen bonds have recently been found in some systems.…”
Section: Introductionmentioning
confidence: 92%
“…This can be primarily attributed to the fact that the polarizability of the X atom becomes larger, and its electronegativity becomes smaller as the size of the chalcogen atom increases. hydrogen bonds [57,58], chalcogen bonds [20,26], and pnictogen bonds [59]. Additionally, the molecular electrostatic surface potential (MESP) [60], quantum theory of atoms in molecules (QTAIM) [61], non-covalent interaction plot (NCIplot) [62], natural bond orbital (NBO) [63], and symmetry-adapted perturbation theory (SAPT) [64] analyses were also conducted to gain a deeper understanding of the π-hole-type chalcogen•••chalcogen interactions.…”
Section: Molecular Electrostatic Surface Potential (Mesp)mentioning
confidence: 99%
“…In addition, as far as we know, no studies have been reported on such interactions containing the heavy chalcogen atom Te as a ChB donor or ChB acceptor. Herein, we used quantum chemical calculations to systematically investigate the strength and nature of the π-hole-type intermolecular chalcogen•••chalcogen interactions in the model complexes between XO 2 (X = S, Se, Te) and CH 3 YCH 3 (Y = O, S, Se, Te), which was frequently used as a nucleophile to engage in various NCIs like hydrogen bonds [57,58], chalcogen bonds [20,26], and pnictogen bonds [59]. Addition-ally, the molecular electrostatic surface potential (MESP) [60], quantum theory of atoms in molecules (QTAIM) [61], non-covalent interaction plot (NCIplot) [62], natural bond orbital (NBO) [63], and symmetry-adapted perturbation theory (SAPT) [64] analyses were also conducted to gain a deeper understanding of the π-hole-type chalcogen•••chalcogen interactions.…”
Section: Introductionmentioning
confidence: 99%
“…These NCIs are crucial for the stability, structure, and function of compounds and proteins containing selenium, as well as for molecular recognition [10][11][12][13][14][15][16][17]. Theoretical and experimental studies have demonstrated that selenium can serve as a proton acceptor to engage in D-H•••Se (D = C, N, O, S) hydrogen bonds (HBs) [18][19][20][21][22][23] and also act as a proton donor to form Se-H•••A (A = N, O, S, Se, π) HBs [24][25][26][27][28]. These selenium-centered hydrogen bonds (SeCHBs) are a significant class of seleniumcontaining NCIs.…”
Section: Introductionmentioning
confidence: 99%